2D Materials: C3N—A 2D Crystalline, Hole‐Free, Tunable‐Narrow‐Bandgap Semiconductor with Ferromagnetic Properties (Adv. Mater. 16/2017). Issue 16 (19th April 2017) - Yang, Siwei; Li, Wei; Ye, Caichao; Wang, Gang; Tian, He; Zhu, Chong; He, Peng; Ding, Guqiao; Xie, Xiaoming; Liu, Yang; Lifshitz, Yeshayahu; Lee, Shuit‐Tong; et al.
Abstract : A new 2D crystalline tunable‐narrow‐bandgap (0.39 eV) semiconductor, C3 N, is developed for the first time, as reported by Guqiao Ding, Xiaoming Xie, Shuit‐Tong Lee, Zhenhui Kang, and co‐workers in article number1605625 . The bandgap tuning (2.74–1.57 eV) of C3 N quantum dots is implemented by varying their size. Back‐gated field‐effect transistors made of single‐layer C3 N show an average I ON / I OFF current ratio of 5.5 × 10 10 . Strikingly, hydrogenated C3 N (C3 NH0.125 ) shows spontaneous magnetism.